Is There Any Association Between Chronic Periodontitis and Anxiety in Adults? A Systematic Review - Aragão, Walessa Alana Bragança; Souza-Monteiro, de Deiweson; Frazão, Deborah Ribeiro; Né, Yago Gecy de Sousa; Ferreira, Railson de Oliveira; Rivera, Luis Felipe Sarmiento; Saito, Miki Taketomi; Rösing, Cassiano Kuchenbecker; Fagundes, Nathalia Carolina Fernandes; Maia, Lucianne Cople; Lima, Rafael Rodrigues (Frontiers in Psychiatry, 2021)
Periodontitis is a multifactorial disease triggered by dysbiotic biofilms, involving the host's immune response, systemic and behavioral factors, including psychosocial conditions. This systematic review aimed to investigate the possible association between periodontitis and anxiety in adults. Searches were performed in PubMed, Scopus, Web of Science, Lilacs, Cochrane, and OpenGrey databases, without language restrictions, considering studies in adults (P-Participants), with (E-Exposure) and without periodontitis (C- Comparison) in an outcome of association with anxiety (O-outcome). Methodological quality assessment was carried out using the Newcastle-Ottawa protocol for case-control and cross-sectional studies, followed by an analysis of the level of evidence using the GRADE tool. Eleven observational studies were selected according to the inclusion criteria from the total of 6,380 studies were retrieved from databases. Eight studies demonstrated higher anxiety levels in subjects with periodontitis, among which only one study presented a high risk of bias. GRADE analysis revealed a low level of evidence State-Trait Anxiety Inventory (STAI); however, since anxiety may affect the quality of life of many subjects, it reinforces the need for further studies that evaluate this association for more extended periods.